1D and 2D Bi Compounds in Field‐Effect Transistors. (14th July 2015) - Uesugi, Eri; Nishiyama, Saki; Akiyoshi, Hidehiko; Goto, Hidenori; Koike, Yoji; Yamada, Kazuyoshi; Kubozono, Yoshihiro
<x xml:space="preserve">Abstract</x> The properties of field‐effect transistors (FETs) with single crystals of Bi compounds, Bi2CuO4 and LaOBiS2, are investigated using an electric‐double‐layer capacitor. The observation of FET characteristics due to electrostatic carrier accumulation is very significant for the field‐induced control of physical properties of these crystals, which may produce the novel physical properties such as superconductivity.